2008
DOI: 10.1152/ajplung.00283.2007
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of purinergic agonist ATPγS against acute lung injury

Abstract: Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are major causes of acute respiratory failure associated with high morbidity and mortality. Although ALI/ARDS pathogenesis is only partly understood, pulmonary endothelium plays a major role by regulating lung fluid balance and pulmonary edema formation. Consequently, endothelium-targeted therapies may have beneficial effects in ALI/ARDS. Recently, attention has been given to the therapeutic potential of purinergic agonists and antagonists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 29 publications
2
47
3
Order By: Relevance
“…In a recent study, it was shown that short-term exposure to low concentrations of sodium arsenide reduced the ability of lung epithelial cells to respond to wound-induced purinergic signaling via both P2X and P2Y receptors (Sherwood et al, 2011). The P2 receptor agonist ATP␥S had a protective effect against acute lung injury induced in a murine model by the bacterial endotoxin LPS (Kolosova et al, 2008). ATP released during mechanical ventilation caused lung injury via P2Y receptors (Matsuyama et al, 2008).…”
Section: Lung Injurymentioning
confidence: 99%
“…In a recent study, it was shown that short-term exposure to low concentrations of sodium arsenide reduced the ability of lung epithelial cells to respond to wound-induced purinergic signaling via both P2X and P2Y receptors (Sherwood et al, 2011). The P2 receptor agonist ATP␥S had a protective effect against acute lung injury induced in a murine model by the bacterial endotoxin LPS (Kolosova et al, 2008). ATP released during mechanical ventilation caused lung injury via P2Y receptors (Matsuyama et al, 2008).…”
Section: Lung Injurymentioning
confidence: 99%
“…The vascular permeability assays were performed as previously described (Kolosova et al, 2008). Evans Blue dye at a dose of 20 mg/kg (body weight) was injected into the mice via the caudal vein 30 min before tissue collection.…”
Section: Determination Of Pulmonary Edemamentioning
confidence: 99%
“…Therefore, agents that protect vascular endothelial cell (EC) 2 barrier properties and vascular integrity may have important therapeutic implications. In prior studies, we detailed the barrier-enhancing effects of bioregulatory molecules such as sphingosine 1-phosphate (S1P) (2,3,4,5,6), hepatocyte growth factor (HGF) (7,1), HMW HA (high molecular weight hyaluronic acid; 8), ATP (9,10), and APC (activated protein C) (11,12,13) via ligation of their cognate receptors resulting in restoration of EC barrier integrity and reduced permeability. HGF promotes angiogenesis and EC barrier function via ligation of c-Met, a cell surface receptor tyrosine kinase, as well as Rac1-dependent cytoskeleton rearrangement (7,1).…”
mentioning
confidence: 99%